A bovine cDNA and a yeast gene (VMA8) encoding the subunit D of the vacuolar H(+)-ATPase. - Nelson, H (1995)
Subunit D of vacuolar H(+)-ATPase (V-ATPase) from bovine chromaffin granules was subjected to partial proteolysis and amino acid sequencing. A cDNA encoding this subunit was isolated and sequenced. The predicted open reading frame encodes a protein of 247 amino acids with a calculated molecular weight of 28,336. Northern blot analysis revealed an mRNA distribution with higher transcript amounts in tissues that are active in secretion. A homologous gene was identified as open reading frame 11 in chromosome V of Saccharomyces cerevisiae. The two proteins exhibit 55% identity with several conservative replacements. Interruption of the yeast gene, denoted as VMA8, resulted in the null mutant delta vma8::URA3 that, like all the other V-ATPase null mutants, did not grow on medium buffered at pH 7.5 and showed no accumulation of quinacrine into their vacuoles. Transformation of the null mutant with a plasmid containing the VMA8 gene restored the wild-type phenotype. This supports the conclusion that subunit D is an integral subunit of the catalytic sector of V-ATPase and its structural analysis suggests analogy to the gamma subunit of F-ATPases.